LEGAL STRATEGIES FOR COMBATING COCKFIGHTING GAMBLING THROUGH PUBLIC LEGAL AWARENESS - Sudirman, Sudirman; Putra, Surya Desismansyah Eka (Masalah-Masalah Hukum, 2024)
This article analyses legal strategies for addressing cockfighting gambling in Indonesia, proposing a shift from repressive law enforcement to an approach based on public legal awareness. Traditionally, efforts to combat cockfighting have been punitive, which often clashes with the local population's views of cockfighting as a hobby or tradition. Employing empirical legal research, this paper investigates shifts in societal views, revealing that cockfighting is increasingly seen as entertainment or cultural practice rather than an illicit gambling activity. The findings suggest legal strategies focused on empowerment, such as promoting rooster breeding for skill and beauty contests, could redirect public enthusiasm from gambling to non-violent forms. This paper advocates for legal reforms prioritizing education and empowerment over raids, aiming to align law enforcement with evolving social attitudes.